Toward Precision Noninvasive Brain Stimulation. - Cappon, Davide B.; Pascual-Leone, Alvaro (American Journal of Psychiatry, 2024)
This document provides a comprehensive overview of the current research and advancements in noninvasive brain stimulation techniques for psychiatric disorders. It emphasizes the importance of personalized treatment approaches that target specific brain circuits to address the diverse symptoms and disabilities experienced by patients. The document discusses the use of techniques such as transcranial magnetic stimulation and transcranial direct current stimulation in the treatment of conditions like depression and Alzheimer's disease. It also explores the potential benefits of home-based interventions and the integration of behavioral and physiological measures in personalized neuromodulation interventions. The future of noninvasive neuromodulation lies in precise targeting methods based on individual brain circuitry disruptions and longitudinal studies to understand long-term effects and predictors of treatment response.